Door-Triggering Mechanism for Large-Scale Rapid-Decompression Experiments. (1st August 2020) - Zhang, Lei; Han, Xiao; Zhang, Xinbin; Yan, Jihong
Abstract : For large-scale rapid-decompression experiments, a new door-triggering mechanism is proposed for a 750 mm diameter pressure relief channel. Quick opening of the door is realized by utilizing a spring-based release mechanism to instantly convert large amounts of elastic potential energy into kinetic energy. To counteract the significant inertial effect of the high-speed door on the chamber, a flywheel-based cushioning mechanism is designed to absorb the kinetic energy of the door after opening. This carefully designed mechanism consists of the closing mechanism, energy storage unit, locking/releasing mechanism, and cushioning mechanism. Kinetic models are established to analyze the dynamic properties. Simulation results reveal that it takes approximately 280 ms for the door to open from 0° to 90°. This work can provide insights for the development of large-scale rapid-decompression equipment in the future.